Effect of Antimalarial Drugs on Plasmodia Cell-Free Protein Synthesis - Ana Ferreras; Ledia Triana; Erlinda Sánchez; Flor Herrera (Memorias do Instituto Oswaldo Cruz, 2002)
A cell-free system from Plasmodium falciparum able to translate endogenous mRNA was used to determine the effect of artemisinin, chloroquine and primaquine on the protein synthesis mechanism of the parasite. The antimalarial drugs did not inhibit the incorporation of [³H] methionine into parasite proteins even at concentrations higher than the ones found to strongly inhibit the parasite growth. Results clearly indicate that these compounds do not have a direct effect on protein synthesis activity of P. falciparum coded by endogenous mRNA.